Enhanced removal of tetracycline from synthetic wastewater using an optimal ratio of co-culture of Desmodesmus sp. and Klebsiella pneumoniae - Jingrui, Xu; Alam, Md. Asraful; Jing, Wang; Wenchao, Wu; Balia Yusof, Zetty Norhana; Daroch, Maurycy; Zhang, Dayong; Lifen, Liu; Mohammad Russel (Elsevier, 2022)
A sustainable approach of Desmodesmus sp. GIEC-179: Klebsiella pneumoniae (DUT-XJR-t-1.2) co-culture ratios were optimized to remove tetracycline (TET) from synthetic wastewater. To enhance the tetracycline removal performance, the effect of microalgae-bacterial co-culture ratio, maximum TET concentration, effective inoculum amount, growth temperature and pH were studied. The optimized ratio 1:2 of Desmodesmus sp.: K. pneumoniae showed the optimal removal percentage at the temperature of 25 °C, pH 7 and 10% inoculum amount; and the removal of TET was recorded as 95%. Moreover, this study explored the Desmodesmus sp.: K. pneumoniae (1:2) nutrient (COD, NH4+ and PO43−) exchange relationship and their interaction of TET removal to better understand their fundamental mechanism. According to the results of this study, Desmodesmus sp.: K. pneumoniae co-culture could be a green option for bio-removal of tetracycline from wastewater.